The status of the coral reefs of the jaffna peninsula (northern sri lanka), with 36 coral species new to sri lanka confirmed by dna bar-coding - Arulananthan, A.; Herath, V.; Kuganathan, S.; Upasanta, A.; Harishchandra, A. (University of Jaffna, 2021)
Sri Lanka, an island nation located off the southeast coast of the Indian sub-continent, has an unappreciated diversity of corals and other reef organisms. In particular, knowledge of the status of coral reefs in its northern region has been limited due to 30 years of civil war. From March 2017 to August 2018, we carried out baseline surveys at selected sites on the northern coastline of the Jaffna Peninsula and around the four largest islands in Palk Bay. The mean percentage cover of live coral was 49 ± 7.25% along the northern coast and 27 ± 5.3% on the islands. Bleaching events and intense fishing activities have most likely resulted in the occurrence of dead corals at most sites (coral mortality index > 0.33). However, all sites were characterised by high values of diversity (H’ ≥ 2.3) and evenness (E ≥ 0.8). The diversity index increased significantly with increasing coral cover on the northern coast but showed the opposite trend on the island sites. One hundred and thirteen species of scleractinian corals, representing 16 families and 39 genera, were recorded, as well as seven soft coral genera. Thirty-six of the scleractinian coral species were identified for the first time on the island of Sri Lanka. DNA barcoding using the mitochondrial cytochrome oxidase subunit I gene (COI) was employed to secure genetic confirmation of a few difficult-to-distinguish new records: Acropora aspera, Acropora digitifera, Acropora gemmifera, Montipora flabellata, and Echinopora gemmacea.
Keywords: Jaffna Peninsula; coral mortality index; DNA barcoding; phylogeny; biodiversity; conservation